A high performance electrochemical deionization method to desalinate brackish water with an FePO4/RGO nanocomposite. Issue 19 (8th May 2018) - Guo, Lu; Huang, Yinxi; Ding, Meng; Leong, Zhi Yi; Vafakhah, Sareh; Yang, Hui Ying
Abstract : Electrochemical deionization (EDI) method achieves excellent deionization performance with a faradaic mechanism, which is a promising technique can be applied in seawater desalination. Abstract : Capacitive deionization (CDI) is a promising technique that may be applied in the desalination of brackish water. However, current CDI technologies suffer from low removal capacity and inapplicability for high concentration brine. Hence, here we introduce a new electrochemical deionization (EDI) method that achieves excellent deionization performance with a faradaic mechanism. In this work, a reduced graphene oxide supported amorphous FePO4 composite (FePO4 @RGO) has been synthesized to work as the anode material due to its high capacity, good electrical conductivity and environmental benignity. Sodium ions in water will be intercalated/deintercalated into or out of the anode material during the charge and discharge process of batch mode experiments, which is different from the physical adsorption of traditional CDI by electrical double layers (EDLs). A high salt removal capacity of 100 mg g −1 has been achieved at a proper flow rate and a current density of 100 mA g −1 with the FePO4 @RGO electrode. Meanwhile, a superior rate performance of 0.117 mg g −1 s −1 has been obtained with a current density of 1000 mA g −1 . The energy consumption of EDI is 3.57 × 10 −4 kW h g −1, which is comparable to those of other CDI technologies.